Deleterious Impact of Donor-Specific Anti-HLA Antibodies Toward HLA-Cw and HLA-DP in Kidney Transplantation. Issue 1 (January 2016) - Bachelet, Thomas; Martinez, Charlie; Del Bello, Arnaud; Couzi, Lionel; Kejji, Salima; Guidicelli, Gwendaline; Lepreux, Sébastien; Visentin, Jonathan; Congy-Jolivet, Nicolas; Rostaing, Lionel; Taupin, Jean-Luc; Kamar, Nassim; et al.
Abstract : Background: It is widely accepted that HLA donor-specific antibodies (DSA) are associated with antibody-mediated rejection and graft loss. However, in many transplant programs, preformed anti–HLA-Cw and anti–HLA-DP DSA are not considered in organ allocation policies because their clinical relevance is still uncertain. Methods: We analyzed the clinical impact of Cw/DP DSA through a retrospective study, comparing 48 patients transplanted with isolated preformed Cw/DP DSA (Cw/DP DSA group) with (i) 104 matched HLA-sensitized kidney transplant recipients with No DSA at D0 (No DSA group) and (ii) 47 kidney transplant recipients with preformed A, −B, −DR, −DQ DSA (A/B/DR/DQ DSA group). Results: A positive flow cytometry crossmatch in the Cw/DP DSA group was more frequent than in the No DSA group and as frequent as in the A/B/DR/DQDSA group. Two years after transplantation, the biopsy-proven acute rejection-free survival was worse in the Cw/DP and A/B/DR/DQ DSA groups than in the No DSA group (65%, 84%, 93%, P = 0.001 and P = 0.05, respectively). Accordingly, graft survival was lower in the Cw/DP and the A/B/DR/DQ DSA groups than in the No DSA group (87%, 89%, 95%, P = 0.02 and P = 0.1, respectively). Conclusions: These results suggest that preformed anti–HLA-Cw and anti–HLA-DP DSA are as deleterious as anti–HLA A/B/DR/DQ DSA. It justifies their inclusion in kidney allocation programs and in immunological risk stratification algorithms. Abstract : Preformed anti-HLA-Cw and anti-HLA-DP DSA are as deleterious as anti-HLA A/B/DR/DQ DSA in terms of biopsy-proven acute rejection, graft function and graft survival and should be considered in kidney allocation programs and in immunological risk stratification algorithms. Supplemental digital content is available in the text.